Is preoperative ciliary body and iris anatomical configuration a predictor of malignant glaucoma development?. (24th January 2013) - Prata, Tiago S; Dorairaj, Syril; De Moraes, Carlos GV; Mehta, Siddhart; Sbeity, Zaher; Tello, Celso; Liebmann, Jeffrey; Ritch, Robert
Abstract Background To investigate anatomical configuration of ciliary body and iris using ultrasound biomicroscopy as a predictor of malignant glaucoma development. Design Retrospective study in a tertiary care hospital. Participants Cohort of 31 consecutive patients diagnosed with post‐surgical malignant glaucoma. Methods Anterior chamber angle, iris and ciliary body configuration of involved eyes that had ultrasound biomicroscopy evaluation prior to the malignant glaucoma onset were evaluated. In cases with no presurgical ultrasound biomicroscopy exam of the involved eye, images from the fellow eye (imaged within 6 months) were analysed. Main Outcome Measures Qualitative parameters. Results Thirty‐one eyes (31 patients) had confirmed malignant glaucoma between 1996 and 2008. Most patients were women (65%) and had an anatomical narrow angle or angle‐closure glaucoma (77%). Mean intraocular pressure at diagnosis was 30.4 ± 13.5 mmHg. The most common operation was trabeculectomy with mitomycin C (55%, 17/31 eyes), combined (3/17) or not (14/17) with cataract extraction and intraocular lens implantation. Among these 31 cases, we were able to evaluate the ultrasound biomicroscopy images of 13 patients (13 eyes) including involved eyes imaged prior to the malignant glaucoma onset or eligible fellow eyes. A narrow angle with or without iridotrabecular contact was found in all eyes. A large and/or anteriorly positioned ciliary body associated with an iris root angulating forward and centrally, revealing a plateau iris configuration, was noticed in 85% (11/13) of these eyes. Conclusion Identification of plateau iris configuration by ultrasound biomicroscopy should be considered as a possible predictor of post‐operative malignant glaucoma development.